A flat petal as ancestral state for Ranunculaceae - Delpeuch, Pauline; Jabbour, Florian; Damerval, Catherine; Schönenberger, Jürg; Pamperl, Susanne; Rome, Maxime; Nadot, Sophie (Frontiers in Plant Science, 2022)
Ranunculaceae comprise ca. 2500 species (ca. 55 genera) that display a broad range of floral diversity, particularly at the level of the perianth. Petals, when present, are often referred to as ‘elaborate’ because they have a complex morphology. In addition, the petals usually produce and store nectar, which gives them a crucial functional role in the interaction with pollinators. Its morphological diversity and species richness make this family a particularly suitable model group for studying the evolution of complex morphologies. Our aims are 1) to reconstruct the ancestral form of the petal and evolutionary stages at the scale of Ranunculaceae, 2) to test the hypothesis that there are morphogenetic regions on the petal that are common to all species and that interspecific morphological diversity may be due to differences in the relative proportions of these regions during development. We scored and analysed traits (descriptors) that characterize in detail the complexity of mature petal morphology in 32 genera. Furthermore, we described petal development using high resolution X-Ray computed tomography in six species with contrasting petal forms (Ficaria verna, Helleborus orientalis, Staphisagria picta, Aconitum napellus, Nigella damascena, Aquilegia vulgaris). Ancestral state reconstruction was performed using a robust and dated phylogeny of the family, allowing us to produce new hypotheses for petal evolution in Ranunculaceae. Our results suggest a flat ancestral petal with a short claw for the entire family and for the ancestors of all tribes except Adonideae. The elaborate petals that are present in different lineages have evolved independently, and similar morphologies are the result of convergent evolution.